Design and construction of a Boost type dc / dc converter with adjustable PWM - Marulanda Durango, Jesser James; Ordoñez, Jhon Jairo; Mosquera Machado, Luis Fernando (Scientia et Technica, 2017)
For the design of the experimental prototype of theboost converter with adjustable PWM, this project was dividedinto 4 stages, the first stage of a study modules oriented teachingpower converters in the second design of the converter isperformed is performed in the third stage the experimentalmodule (construction adjustable PWM is constructed, whosepurpose is to make changes in real time on the circuit, frequencyand variable duty cycle, construction of the power circuit withthe specifications given finally designs converter housing) in thefourth stage the theoretical and practical module values areanalyzed.